Optimizing Ship Diesel Engine Performance: A Comparative Analysis of Fuel Atomizer Performance and PMS Practices Among ANT and ATT Students at STIP Jakarta - Baihaqi Baihaqi; April Gunawan Malau; Marudut Bernadtua Simanjuntak (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research investigates the influence of fuel atomizer performance on maintaining ship diesel engine performance, focusing on ANT (Nautika - Deck Officers) and ATT (Teknika - Engine Officers) students at STIP Jakarta. The study aims to analyse the practices related to the Planned Maintenance System (PMS) and their impact on fuel atomizer performance among these student officers. Qualitative research methods, including questionnaires, were employed to collect data from ANT and ATT students. The Likert scale was used to measure attitudes, opinions, and perceptions regarding fuel atomizer performance and PMS practices. The research highlights the critical role of fuel atomizers in diesel engine optimization and underscores the importance of effective PMS practices. The findings provide valuable insights for enhancing ship diesel engine performance through improved maintenance strategies.